2022
DOI: 10.1186/s12913-022-08578-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting—stillbirth and neonatal death audit in Malawi: a qualitative study

Abstract: Background Over one million babies are stillborn or die within the first 28 days of life each year due to preventable causes and poor-quality care in resource-constrained countries. Death audit may be a valuable tool for improving quality of care and decreasing mortality. However, challenges in implementing audit and their subsequent action plans have been reported, with few successfully implemented and sustained. This study aimed to identify factors that affect stillbirth and neonatal death au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…We also observed variations among hospitals in terms of the management of necessary medications and supplies. This could be because the hospitals typically execute an incomplete drug assessment plan before placing orders from the central medical store, In a qualitative study which examined the facilitators and barriers to implementing stillbirth and neonatal death audit [56], causes of insufficient supplies included limited facility autonomy and decision-making powers despite decentralisation, one sole supplier for drugs and essential drugs with limited powers to outsource if they were not available, and inadequate leadership support. Financial support also remained inadequate in the facilities, which depended on external donors to fund activities, resources and equipment.…”
Section: Guidelines and Standards Implementationmentioning
confidence: 99%
“…We also observed variations among hospitals in terms of the management of necessary medications and supplies. This could be because the hospitals typically execute an incomplete drug assessment plan before placing orders from the central medical store, In a qualitative study which examined the facilitators and barriers to implementing stillbirth and neonatal death audit [56], causes of insufficient supplies included limited facility autonomy and decision-making powers despite decentralisation, one sole supplier for drugs and essential drugs with limited powers to outsource if they were not available, and inadequate leadership support. Financial support also remained inadequate in the facilities, which depended on external donors to fund activities, resources and equipment.…”
Section: Guidelines and Standards Implementationmentioning
confidence: 99%
“…The decline in Malawi's neonatal mortality rate can be attributed to the collaborative efforts of multiple sectors through strengthening infrastructure, space, staff, equipment, medications, and hospital care delivery and scaling up effective interventions targeting the major causes of neonatal mortality [12][13]. Despite the literature indicating that delivery in a health facility can reduce the risk of neonatal mortality by 29% in low-and middle-income countries [14][15][16], other studies have demonstrated that reductions in neonatal mortality require capacitated health facilities with su cient infrastructure, health workforce, equipment and diagnosis and treatment systems to demonstrate decreased mortality [17][18]. For example, despite 90% of deliveries occurring in a health facility in Malawi [19], many vital inputs to reduce neonatal mortality are missing, likely linked to the slowed neonatal mortality rate [20].…”
Section: Introductionmentioning
confidence: 99%